Role of nutraceuticals in viral infections as immunomodulators: A comprehensive review - Sunanda Biswas; Souti Biswas; Gopalakrishnan PadmaPriya; Jaspreet Kaur; Atreyi Pramanik; Fakhar Islam; Fatima Tariq; Ali Imran; Mohd Asif Shah (eFood)
Abstract Nutraceuticals are dietary supplements produced from food sources that are intended to improve health through immune system modulation or by helping to prevent and treat a variety of ailments. Their anti‐inflammatory, immunomodulatory, and antioxidant qualities are well recognized. In certain instances, they even show direct microbiological efficacy against viral infections. Because of their special capacity, they may be able to help slow the spread and effects of very infectious illnesses, such as pandemics like COVID‐19. Nutraceuticals work well against viral infections because of a number of intricate processes. Reducing the harm that infections do to the immune system is one of the main effects. Nutraceuticals have the power to stimulate and activate the immune system, improving the body's capacity to identify and eliminate infections. Additionally, they are essential in reducing oxidative damage, which can result in serious consequences and is frequently intensified during viral infections. Nutraceuticals also strengthen immunity by promoting regulatory T cell differentiation and proliferation, which is crucial for preserving immune system homeostasis and limiting hyperinflammatory reactions. They control the production of proinflammatory cytokines, which helps to avoid cytokine storms during viral infections that may seriously harm tissue. This regulation lowers the danger of hyperinflammation and enhances overall results by supporting a balanced immune response. Through a number of biochemical mechanisms, nutraceuticals can strengthen the body's defenses against viral infections. They promote a more effective and efficient immune response by regulating immune cell activities, oxidative stress reduction, and antioxidant pathway activation. Furthermore, by interacting with different cellular signaling pathways, nutraceuticals can affect the synthesis and function of important immune components. This study clarifies the molecular processes behind the immunomodulatory effects of nutraceuticals, highlighting their crucial role in both treating and preventing viral infections.